2018
DOI: 10.1371/journal.pone.0204009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity determinants and contribution of fish to maternal and under-five nutritional status in Zambia

Abstract: BackgroundThis study examines socio-economic determinants of food consumption patterns amongst women of reproductive age and children aged 6–59 months from urban poor settlements of Lusaka and their implications for nutritional status. Particular emphasis was placed on the role of fish in their diets and nutritional status.MethodsA cross-sectional survey design was applied, in which 714 mother-child dyads, with children aged 6–59 months were enrolled. A three-stage randomized cluster sampling approach was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 36 publications
5
79
2
1
Order By: Relevance
“…Studies have shown that dietary diversity was positively associated with the child's age (Iqbal, Zakar, Zakar, & Fischer, ), maternal education, socio‐economic status (Marinda, Genschick, Khayeka‐Wandabwa, Kiwanuka‐Lubinda, & Thilsted, ; Patel et al, ; Senarath et al, ; Solomon, Aderaw, & Tegegne, ), mother's working status (Solomon et al, ), women's empowerment (Ickes, Wu, Mandel, & Roberts, ), and the number of antenatal care (ANC) visits (Patel et al, ). There are reports of differences in consumption of ASF by residence and wealth status and child's age (J. M. White et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that dietary diversity was positively associated with the child's age (Iqbal, Zakar, Zakar, & Fischer, ), maternal education, socio‐economic status (Marinda, Genschick, Khayeka‐Wandabwa, Kiwanuka‐Lubinda, & Thilsted, ; Patel et al, ; Senarath et al, ; Solomon, Aderaw, & Tegegne, ), mother's working status (Solomon et al, ), women's empowerment (Ickes, Wu, Mandel, & Roberts, ), and the number of antenatal care (ANC) visits (Patel et al, ). There are reports of differences in consumption of ASF by residence and wealth status and child's age (J. M. White et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews in 2019 and 2015concluded that depressed women breastfed their child for shorter duration than nondepressed women [23,41]. Other previous studies also reported a negative association between maternal depression and early initiation of breastfeeding [42], complementary feeding initiation [43] and infants' dietary diversity [44,45].…”
Section: Discussionmentioning
confidence: 96%
“…A major goal of this work was to develop and assess an RUSF to contain fish oil as a method to deliver macronutrient and micronutrient supplements and DHA to women at risk for food insecurity and malnutrition during pregnancy and lactation since this is a concern in Zambia [ 5,29]. The lipid based nutrient supplements are deemed a valid delivery vehicle for DHA as the oils are miscible in the nut paste, low in water, as well as air and light tight, which helps to maintain the integrity of the highly unsaturated fatty acids to prevent or reduce oxidation [30].…”
Section: Rusf Formulationmentioning
confidence: 99%
“…Improving maternal and infant nutrition and health is a major focus of the Zambian Government to ensure the population reaches its full potential [1,4]. However, the dietary diversity for women and children in Zambia is highly dependent upon socioeconomic status, such that a low diversity index correlates with malnutrition and food insufficiency [5,6]. Animal-source foods are limited and the diet is highly dependent on starchy staples such as the corn-based porridge, nshima.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation